Reversed-phase high-performance liquid chromatography: A fast and efficient analytical method to quantify docetaxel-loaded pegylated liposomes in release study - Aires-Fernandes, Mariza [UNESP]; Eloy, Josimar O.; Damiani Victorelli, Francesca [UNESP]; Scanavez Ferreira, Paula [UNESP]; Pironi, Andressa Maria [UNESP]; Chorilli, Marlus [UNESP] (Wiley, 2021)
Docetaxel is an anticancer that belongs to the family of taxanes and acts in the inhibition of cell proliferation through the polymerization of microtubules. The aim of this study was the development and validation of a fast method by reversed-phase high-performance liquid chromatography for quantitative analysis of docetaxel encapsulated in pegylated liposomes. The analytical method was validated for the following recognized specifications: system suitability, precision (repeatability and intermediate precision), linearity, accuracy, selectivity, detection and quantification limits, and robustness. The reversed phase-high-performance liquid chromatography analyses were performed at a temperature of 45°C (isocratic mode). The mobile phase was composed of acetonitrile and water (65:35, v/v) and the flow rate was fixed at 0.8 mL/min. The running time and wavelength were 8 min and 230 nm, respectively. The method was found to be linear, precise, selective, precise, robust, accurate, in the range of 1–75 μg/mL (R2 = 0.9999) and the values of detection and quantification limits were 2.35 and 7.84 μg/mL, respectively. The release rates of docetaxel in pegylated liposomes were lower compared to docetaxel in solution. The reversed phase high-performance liquid chromatography method developed proved to be adequate and can be effectively used to determine the in vitro release profile of docetaxel transported by pegylated liposomes.
Keywords: docetaxel; in vitro release; liposomes; method validation; reversed-phase high-performance liquid chromatography